Islam Wasathiyah dalam Wacana Tafsir Ke-Indonesia-an (Studi Komparatif Penafsiran M. Quraish Shihab dan Buya Hamka) - Adam Tri Rizky; Ade Rosi Siti Zakiah (Fakultas Ushuluddin, Adab dan Dakwah, Institut Agama Islam Negeri Pekalongan, 2020)
Basically, the Qur'an is predetermined. What is the ideal position of Muslims to behave. This ummah is called ummatan wasathan. Even so, in real life Muslims are still far from the values ​​of the ummahatan wasathan. Therefore, this study tries to study the ummah of wasathan according to Quraish Shihab in Tafsir al-Misbah and Buya Hamka in Tafsir al-Azhar. The aim is to understand the interpretation and concept of Ummatan Wasathan according to the two figures, as well as the relevance of the interpretation concept to the values ​​of Pancasila. Literature research. This research uses documentation techniques and descriptive-analytical methods. This research also uses the comparison method. The results of this study were obtained from: according to Quraish Shihab and Buya Hamka, ummatan wasathan were: (a) People who have the power of faith who need istiqomah towards Allah and His Messenger; (B) Wise people who have common sense; (c) A people who love unity and unity; (d) Inclusive people; role model, and fair; (e) People who have a high balance or stability. The concept of M. Quraish Shihab and Buya Hamka's interpretation of the Ummah wasathan is very relevant to the basis of the Republic of Indonesia, namely Pancasila.